2019
DOI: 10.1038/s41598-019-50494-5
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity Cu(I) chelator PSP-2 as potential anti-angiogenic agent

Abstract: Copper is an essential trace metal that has been implicated in angiogenesis, the formation of new blood vessels. As tumor growth relies on establishing a functional capillary network for blood supply, copper chelation therapy may hold promise as an anti-cancer strategy by suppressing angiogenesis. To test the anti-angiogenic effect of PSP-2, a recently developed high affinity Cu(I) chelator with low zeptomolar dissociation constant, we utilized the endothelial cancer cell line EAhy926 and assessed changes in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…We reasonably speculated that cuproptosis, a recently defined form of cell death, is correlated with glioma prognosis. Although the mechanisms underlying cuproptosis have not been determined, increasing evidence has indicated the significant role played by copper in tumour development and immunity: An increasing number of studies have shown that copper‐induced tumour cell death was associated with mitochondrial dysfunction, proteasome inhibition and antiangiogenesis 37–40 . Furthermore, intratumoral copper can regulate key signalling pathways that mediate PD‐L1‐driven cancer immune evasion 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reasonably speculated that cuproptosis, a recently defined form of cell death, is correlated with glioma prognosis. Although the mechanisms underlying cuproptosis have not been determined, increasing evidence has indicated the significant role played by copper in tumour development and immunity: An increasing number of studies have shown that copper‐induced tumour cell death was associated with mitochondrial dysfunction, proteasome inhibition and antiangiogenesis 37–40 . Furthermore, intratumoral copper can regulate key signalling pathways that mediate PD‐L1‐driven cancer immune evasion 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms underlying cuproptosis have not been determined, increasing evidence has indicated the significant role played by copper in tumour development and immunity: An increasing number of studies have shown that copper-induced tumour cell death was associated with mitochondrial dysfunction, proteasome inhibition and antiangiogenesis. [37][38][39][40]…”
Section: Discussionmentioning
confidence: 99%
“…For automated methods, many software packages exist which can be adapted to identify tubules, vessel branch points and network junctions. Such software packages include: Angiotool [ 221 ], AngioQuant [ 60 , 73 , 137 ], Wimasis [ 87 , 101 ], HetCAM [ 222 ], Photoshop CS4 [ 223 ] and Synedra view [ 224 ]. Image analysis software such as Image J can be used for both manual and semi-automated quantification methods.…”
Section: Cam Analysesmentioning
confidence: 99%
“…Previously, our research group reported on the anti-angiogenic effects of the novel membrane-permeant high-affinity Cu(I) chelator PSP-2 [ 33 ], which binds Cu(I) with low zeptomolar affinity. We demonstrated that PSP-2 adversely affects tube formation of tumorigenic endothelial cells EAhy926 in vitro, impaired normal sprouting in the aortic ring assay, and resulted in suppressed branching, in favor of long, parallel arranged vessels in the chorioallantoic membrane of the chicken embryo (CAM assay) in ovo [ 33 ]. In the current study, we directly explored the potential anti-tumorigenic action of PSP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Tetrathiomolybdate was also combined with radiotherapy and proved effective in a mouse Lewis lung metastatic tumor model [ 31 ]. Recently, our research team evaluated a new high-affinity Cu(I) chelator, PSP-2 [ 32 ], for its potential anti-angiogenic activity in vitro and in ovo, i.e., in the chorioallantoic membrane assay of the chicken embryo (CAM assay) [ 33 ]. We were able to show a significant reduction in angiogenic activity when PSP-2 was applied.…”
Section: Introductionmentioning
confidence: 99%